Biological Activity of Hedyotis Spp. and Chemical Constituents of Hedyotis Capitellata - Ahmad, Rohaya (2005)

(untitled)
Hedyotis (Family, Rubiaceae) is a genus of erect decumbent or climbing herbs. The genus consists of some 180 species. They grow well on dry and sandy soil, along rivers and coasts and in the forests. There are 35 species recorded in Malaysia. Most of the species possess medicinal properties and are used by the Malay as well as the Chinese communities. The methanolic extracts of seven Hedyotis species including H. capitellata (stems, leaves and roots), H. dichotoma (aerial parts and roots), H. verticillata (leaves and stems), H. herbacea (aerial parts), H. pinifolia (aerial parts), H. corymbosa (aerial parts) and H. nudicaulis (aerial parts) were screened for antioxidant, radical- scavenging, anti-inflammatory, cytotoxic as well as anti-bacterial properties using the ferric thiocyanate (FTC) and thiobarbituric acid (TBA), the diphenylpicryl hydrazyl (DPPH), the Griess assay, the MTT assay and the disc diffusion methods, respectively. The results showed that all of the extracts tested possess strong antioxidant potential. However, they are poor radical scavengers and nitric oxide inhibitors. They are also found to be weakly cytotoxic and possess weak to moderate antibacterial properties. On the basis of the screening results and literature review, H. capitellata (stems) was selected for further phytochemical study. Phytochemical investigation on the active fraction of the stems of H. capitellata plant yielded fifteen compounds. The structure of the compounds was elucidated based on spectroscopic techniques and comparison with literature values. Eight compounds are new furanoanthraquinones named capitellataquinone A-G and epi- capitellataquinone E. A new anthraquinone, 2,8-dihydroxy-1-methoxyanthraquinone together with rubiadin, alizarin 1-methyl ether, anthragallol 2-methyl ether, digiferruginol and scopoletin were also isolated. From the roots of the plant, lucidin 3-O-β-glucoside was also isolated. The isolation of an anthraquinone glycoside is a first for the genus. Antioxidant assays on ten compounds including capitellataquinones A, B, E, F, epi- capitellataquinone E, rubiadin, alizarin 1-methyl ether, anthragallol 2-methyl ether, digiferruginol and scopoletin showed that capitellataquinone A and scopoletin possess strong antioxidant properties with percent inhibition of 94-96% compared to quercetin (98%). MTT cytotoxic assays of the same compounds tested showed weak cytotoxicity to most cell-lines with IC50 values of 24-40 μg/ml. However, alizarin 1- methyl ether was found to be selectively cytotoxic against MDA-MB-231 with an IC50 value of 8 μg/ml.